Menganalisis pola dan arah aliran hujan di Negeri Sembilan menggunakan kaedah GIS poligon thiessen dan kontur isoyet - Shaharuddin Ahmad,; Noorazuan Md. Hashim, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2006)
Rainfall frequency and duration are important indices in the field of geomorphology, hydrology and slope studies. Information about rainfall distribution is also important to mankind due to its role in infuencing various human activities such as agriculture, fishing and tourism. This article analyses the patterns and trends of rainfall in the state of Negeri Sembilan, Peninsular Malaysia. Monthly and annual rainfall data for the 21-years period (1983-2003) were supplied by the Malaysian Meteorological Services (MMS) for the whole eight climatology stations of the state. GIS Polygon Thiessen and isohyetal contour methods were employed to calculate and determine the rainfall pattern, while the Mann-Kendall’s test was used to establish changes in trends and variability of rainfall. Based on the percentile and isohyetal contour methods used the distribution pattern of rainfall in Negeri Sembilan can be categorised into two types, namely, medium wet area (stretching from Jelebu-Kuala Pilah to Gemencheh) and heavy rainfall area (at and around coastal area-Seremban-Chembong). A pattern of inconsistency in rainfall changes was observed at all climatology stations for the observed period. Based on the Mann-Kendall’s test, the years of 1980s and 1990s were established as years of changes in rainfall distribution at all climatology stations. These changesmay significantly affect the amount of water in the catchment area, thus determining the water supply, and may be linked to local factors such as accelerated regional development and global factors such as global climate change